Emphysematous pyelonephritis in a transplanted kidney - Cristiano Claudino Oliveira; Paula Dalsoglio Garcia; Rosa Marlene Viero (University of São Paulo, 2016)
Emphysematous pyelonephritis is a rare infection characterized by necrosis and gas accumulation in the renal parenchyma, adjacent tissues, and/or urinary collecting system. This entity is rarely reported in transplanted kidneys. Computed tomography imaging is necessary for diagnosis and risk classification. The authors described the case of a 58-year-old man who underwent a kidney transplant and presented sepsis from a urinary tract infection. An abdominal tomography showed some characteristics of emphysematous pyelonephritis associated with an abscess. A graft biopsy, performed 45 days after the transplant, failed to show signs of infection, and tubule-interstitial and vascular rejection were ruled out. The patient had a poor outcome, and a nephrectomy was needed, the pathological analysis of which yielded the diagnosis of chronic pyelonephritis with necrotizing papillitis. The patient became hemodynamically unstable and died. The authors highlight the current tomographic criteria for the diagnosis and treatment of emphysematous pyelonephritis and question the validity of accepting the same standards used to guide the treatment of patients without transplants, and call attention to the importance of the clinical status for the indication of nephrectomy in cases of emphysematous pyelonephritis